Surgical treatment of epilepsy due to cortical dysplasia: clinical and EEG findings. - Hirabayashi, S (1993)
Seventeen patients with cortical dysplasia who had surgical resection for medically intractable partial epilepsy were studied. Compared with two groups of surgically treated patients with intractable epilepsy due to tumour (n = 20) and mesial temporal sclerosis (n = 40), patients with cortical dysplasia showed significantly more frequent extratemporal lesions, more frequent non-epileptiform EEG abnormalities and less favourable surgical outcome for seizure control. Patients with cortical dysplasia were younger at onset of seizures and had a lower detection rate of CT abnormalities compared with the tumour group, and lower IQ compared with the mesial temporal sclerosis group. MRI was abnormal in five of seven patients. Six patients became seizure-free or almost seizure-free but eight did not experience relief of seizures. Surgical outcome related to the extent of pathology but not to the histological abnormality. Lesions outside the temporal and frontal lobes were correlated with poor surgical outcome, as were generalised interictal EEG abnormalities, which may reflect extensive or multiple lesions. Ictal intracranial recordings were not useful for presurgical evaluation of cortical dysplasia.